1992
DOI: 10.1113/jphysiol.1992.sp019118
|View full text |Cite
|
Sign up to set email alerts
|

GTP‐binding protein involvement in membrane currents evoked by carbachol and histamine in guinea‐pig ileal muscle.

Abstract: SUMMARY1. Single smooth muscle cells obtained by enzymic dispersion of the longitudinal muscle layer of guinea-pig ileum were used for recording membrane currents under whole-cell voltage clamp in response to carbachol (100 /bM, unless otherwise stated) or histamine (100 jam) applied extracellularly.2. At a holding potential of 0 mV, a transient outward current was evoked by carbachol and histamine. Responses to the two agonists were very similar in size and time course to the current response to caffeine (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 32 publications
6
132
0
Order By: Relevance
“…This was supported by the failure of Ga i1 , Ga i1 /Ga i2 , Ga q /Ga 11 and Ga s antibodies to reduce the cation current response. These results are also consistent with the block of the cation current response to M 2 receptor activation by PTX (Inoue & Isenberg, 1990;Komori et al, 1992;Unno et al, 1995;Pucovsky et al, 1998). The failure of Ga q /Ga 11 antibodies to inhibit mIcat is significant because Wang et al (1997) recently showed that dialysis of the same antibody inhibited muscarinic-receptor I Cl(Ca) in tracheal smooth muscle cells, although it had no effect on mIcat.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This was supported by the failure of Ga i1 , Ga i1 /Ga i2 , Ga q /Ga 11 and Ga s antibodies to reduce the cation current response. These results are also consistent with the block of the cation current response to M 2 receptor activation by PTX (Inoue & Isenberg, 1990;Komori et al, 1992;Unno et al, 1995;Pucovsky et al, 1998). The failure of Ga q /Ga 11 antibodies to inhibit mIcat is significant because Wang et al (1997) recently showed that dialysis of the same antibody inhibited muscarinic-receptor I Cl(Ca) in tracheal smooth muscle cells, although it had no effect on mIcat.…”
Section: Discussionsupporting
confidence: 79%
“…In rabbit portal vein myocytes, the cation current evoked by noradrenaline shows similar properties to mIcat in guinea-pig small intestine at negative potentials but, unlike the latter, passes little current in the positive range (Helliwell & Large, 1996); it can be evoked by 1-oleoyl-2-acetyl-sn-glycerol (OAG) (Helliwell & Large, 1997), which is completely ineffective in evoking mIcat in the guinea-pig intestine (our unpublished observation). mIcat in guinea-pig small intestine is pertussis toxin (PTX)-sensitive (Inoue & Isenberg, 1990;Komori et al, 1992), as it is in equine tracheal smooth muscle cells (Wang et al, 1997). In the latter, the current was blocked by Ga i1 /Ga i2 antibodies and by Ga i3 /Ga o antibodies, but not by Ga q /Ga 11 antibodies, suggesting that Ga i /Ga o was the link between muscarinic receptor and cation channel.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The longitudinal muscle layer of the segments was peeled from the underlying circular muscle and washed in physiological salt solution (PSS; composition given below). Smooth muscle cells were dispersed by a combination of collagenase (0.2-0.6 mg ml-') and papain (0.3-0.6 mg ml-'), as previously described (Komori et al, 1992 (Pacaud & Bolton, 1991;Komori et al, 1993) (Komori et al, 1992;1993; (Komori et al, 1993;Kohda et al, 1996).…”
Section: Preparation Of Cellsmentioning
confidence: 99%
“…Carbachol (CCh) is capable of inducing InsP3-dependent [Ca2+], oscillations in single smooth muscle cells of guinea-pig ileum (Komori et al, 1993;Kohda et al, 1996). The present study aimed to investigate potential path- (Benham et al, 1985;Inoue & Isenberg, 1990;Komori et al, 1992) and can change its intensity in a manner closely correlated with [Ca2+]i (Pacaud & Bolton, 1991; Brifish Journal of Phamacology (1996Phamacology ( ) 119, 245 252 1993 …”
Section: Introductionmentioning
confidence: 99%